Time-series transcriptome of Brachypodium distachyon during bacterial flagellin-induced pattern-triggered immunity - Ogasahara, Tsubasa; Kouzai, Yusuke; Watanabe, Megumi; Takahashi, Akihiro; Takahagi, Kotaro; Kim, June-Sik; Matsui, Hidenori; Yamamoto, Mikihiro; Toyoda, Kazuhiro; Ichinose, Yuki; Mochida, Keiichi; Noutoshi, Yoshiteru (Frontiers in Plant Science, 2022)
Plants protect themselves from microorganisms by inducing pattern-triggered immunity (PTI) via recognizing microbe-associated molecular patterns (MAMPs), conserved across many microbes. Although the MAMP perception mechanism and initial events during PTI have been well-characterized, knowledge of the transcriptomic changes in plants, especially monocots, is limited during the intermediate and terminal stages of PTI. Here, we report a time-series high-resolution RNA-sequencing (RNA-seq) analysis during PTI in the leaf disks of Brachypodium distachyon. We identified 6,039 differentially expressed genes (DEGs) in leaves sampled at 0, 0.5, 1, 3, 6, and 12 hours after treatment (hat) with the bacterial flagellin peptide flg22. The k-means clustering method classified these DEGs into 10 clusters (6 upregulated and 4 downregulated). Based on the results, we selected 10 PTI marker genes in B. distachyon. Gene ontology (GO) analysis suggested a tradeoff between defense responses and photosynthesis during PTI. The data indicated the recovery of photosynthesis started at least at 12 hat. Over-representation analysis of transcription factor genes and cis-regulatory elements in DEG promoters implied the contribution of 12 WRKY transcription factors in plant defense at the early stage of PTI induction.